2017
DOI: 10.1158/2326-6066.cir-17-0229
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer T-cell Immunotherapy in Combination with Chemotherapy-Induced Immunogenic Cell Death Targets Metastatic Breast Cancer

Abstract: Natural killer T (NKT) cells are glycolipid-reactive lymphocytes that promote cancer control. In previous studies, NKT-cell activation improved survival and antitumor immunity in a postsurgical mouse model of metastatic breast cancer. Herein, we investigated whether NKT-cell activation could be combined with chemotherapeutic agents to augment therapeutic outcomes. Gemcitabine and cyclophosphamide analogues enhanced the potential immunogenicity of 4T1 mammary carcinoma cells by increasing the expression of anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 50 publications
2
43
0
1
Order By: Relevance
“…These observations are in line with previous studies, which have demonstrated that cyclophosphamide does not induce any significant changes in the total numbers of these different cell subsets. 34 Although it was reported that cyclophosphamide has immunostimulatory activities 39,40 and can induce the activation of CD4 + and CD8 + T cells, including iNKT cells, 34 its administration alone in our B-cell lymphoma model did not have any antitumor effect (Figure 3(c)), in line with previous data. 34 The combination treatment with NKT14m antibody and cyclophosphamide resulted in a greater antitumor effect compared to either treatment alone (Figure 3(c)).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These observations are in line with previous studies, which have demonstrated that cyclophosphamide does not induce any significant changes in the total numbers of these different cell subsets. 34 Although it was reported that cyclophosphamide has immunostimulatory activities 39,40 and can induce the activation of CD4 + and CD8 + T cells, including iNKT cells, 34 its administration alone in our B-cell lymphoma model did not have any antitumor effect (Figure 3(c)), in line with previous data. 34 The combination treatment with NKT14m antibody and cyclophosphamide resulted in a greater antitumor effect compared to either treatment alone (Figure 3(c)).…”
Section: Discussionsupporting
confidence: 89%
“…34 Although it was reported that cyclophosphamide has immunostimulatory activities 39,40 and can induce the activation of CD4 + and CD8 + T cells, including iNKT cells, 34 its administration alone in our B-cell lymphoma model did not have any antitumor effect (Figure 3(c)), in line with previous data. 34 The combination treatment with NKT14m antibody and cyclophosphamide resulted in a greater antitumor effect compared to either treatment alone (Figure 3(c)). In contrast to previous studies using α-GalCer, 34 iNKT-cell activation with NKT14m antibody seems to be more potent and its combination with a chemotherapeutic agent, such as cyclophosphamide, has a synergistic activity increasing IFN-γproducing iNKT and T cells (Figure 3(d)-(f)), and establishing a long-lasting memory (Figure 4(b)), suggesting that this combination could foster a coordinated antitumor response which translates into a better outcome.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, in the last few years, several reports has been published about stem cell-derived NK cells that may have a better cytotoxic effect against tumor cells [36,37]. Furthermore, the combination with chemotherapy might lead to higher responses in metastatic breast cancer patients [38].…”
Section: Passive Vaccinationmentioning
confidence: 99%